Why the moral enhancements of character are doomed to fail? The critique of the virtue ethics accounts - Καλοκαιρινού (Eleni Kalokairinou) Ελένη (Bioethica, 2018)
All kinds of enhancements, cognitive, physical, psychological, moral etc. are at the center of moral debates nowadays. In particular the moral enhancements of character by virtue of pharmacological and biotechnological means are widely discussed, as they raise a number of questions regarding human autonomy and freedom. In the present article, we argue that if we study carefully the way in which the moral enhancements are applied according to the bioethicists Julian Savulescu and Ingmar Persson, we will realize that they are logically impossible. That is, if we analyze the logical procedure of enhancing characters morally, as this is presented in Aristotle’s and Kant’s moral account, then we will understand that the kind of moral enhancement of character by virtue of biotechnological means which the two philosophers put forward is doomed to fail. Furthermore, we will also understand that the two philosophers offer an impoverished conception of morality, since reason, the basic element of the moral process, plays no role in the account of moral reasoning they propound.